Sourcing and deploying new crop varieties in mountain production systems - Sthapit, B.; Gauchan, D.; Sthapit, S.; Hari Ghimire, K.; Joshi, B.K.; Santis, P. de; Jarvis, Devra I. (Routledge, 2019)
Farmers continue to grow traditional crop varieties, along with now-creolized varieties released decades ago. The absence of modern varieties is due to the failure of conventional plant breeding to meet production/cultural needs, difficult access to new varieties, and inadequate safety-nets for testing new varieties in the field. We hypothesize a portfolio of varieties offering several functional traits not found in the varieties currently grown. After a literature review comparing conventional and participatory methods for sourcing and deploying new varieties, we test the potential of an heuristic framework as a decision-making tool to provide farmers with diversity-rich solutions for managing environmental variability and biotic and abiotic production constraints, and to broaden the genetic base of traditional crop diversity for enhancing system resilience. The pros and cons of various methods, as well as production constraints and institutional capacity, are taken into consideration. Participatory variety selection and participatory tool kits emerge as simple methods for sourcing and deploying new crop diversity which can reach greater numbers of farmers in risk-prone mountain environments. We also note the contributions of participatory seed exchange in consolidating seed networks and exchanges among farming communities.